Influences of a Quasi-stationary Front on Particulate Matter in the Low-latitude Plateau Region in China - Wenxuan Fan; Jian Wu; Xiaopeng Li; Fangyuan Yang; Bing Chen; Jun Guo (Aerosol and Air Quality Research)
Abstract By utilizing observation and reanalysis data and statistical methods to comprehensively assess the main characteristics of particulate matter (PM) on the low-latitude plateau (LoLaP) of southwestern China, this study analyzed the influence of the Kunming quasi-stationary front (KMQSF) on the PM concentration during winter in this region. We found that the location and intensity of the KMQSF significantly affected the distribution pattern of the PM and induced high concentrations in some areas during a typical pollution event in 2016. Furthermore, we investigated all of the KMQSF synoptic weather that occurred from 2014 till 2019 and categorized it into nine types, which produced different pollution patterns. When the KMQSF moved westward from the center of the LoLaP, the easterly wind transported PM to the western part of the region, which led to an increase in the mean daily PM10 and PM2.5 concentrations in Kunming, a capital city in that area; simultaneously, however, the PM10 and PM2.5 levels remained high in Guiyang, a capital city in the eastern part of the LoLaP. When the KMQSF gradually retreated from the western to the eastern part of the LoLaP, the PM in Kunming dropped as the westerly wind increased in strength, whereas the PM in Guiyang continued to rise as the planetary boundary layer (PBL) height (PBLH) and boundary layer dissipation (BLD) rate decreased. When the KMQSF disappeared, temperature inversion, a shallow PBL and weak BLD across the entire region caused pollutants to accumulate, resulting in the highest mean daily PM10 and PM2.5 concentrations for both cities.